Letramento funcional em saúde de idosos - Romero, Samuel Salvi (2017)
Human aging is a world reality, like in Brazil. Health needs of the population require a new way of work in the health assessments. The objective of this study, it was to evaluate the level of functional literacy in the health of elderly people living in t he urban area of the town of Severiano de Almeida, in the north of state of Rio Grande do Sul. This study it was characterized as a Mixed research design, the combination of quantitative and qualitative data, follows the model of convergence or fusion in the research analysis. The data collection it was performed in the households of the elderly participants of this study, which totalled 175 participants, in which the quantitative data obtained by the application of the instrument S TOFHLA (short version), It was collected concomitantly with the qualitative data, obtained through an open interview. The sociodemographic and clinical characteristics it was presented through descriptive statistics. The continuous variables were presented by mean and standard deviation, median, percentiles, maximum value and minimum value. The level of functional literacy it was stratified according to the correctness described in the classification of the scores. In order to verify the association between health functional literacy and sociodemographic and clinical variables, Pearson's Chi-square test and Fisher's exact test α = 5% and p ≤ 0.05, it was used. The analysis of the data it was performed by SPSS software (version 20.0). The interview, which composed the qualitative data, the data it was interpreted following the content thematic analysis proposal. The results of the analysis of the quantitative data and the results of the analysis of the qualitative data it was jointly interpreted leading to the greater comprehensive ness of the studied phenomenon and the deepening of the discussion. The result of this research it was a scientific production that aimed to characterize the elderly profile regarding the level of LFS, as well as its association with sociodemographic and clinical variables, to understand the impact of these results on the health behaviour of the elderly of this study. A category it was developed, based on the analysis of the open interviews and from these subcategories were designed, constituting the configuration of the oldaged, that it was studied. The subcategories were denominated of: Role of the Health Professional, family support and friends; Custom and subjectivity. The result of the LFS level evaluation showed a majority of elderly people with inadequate health literacy (39.4%). The results associated with the sociodemographic and clinical variables showed an association between LFS and the variables gender; Age group; Origin; Schooling, and number of children (p ≤ 0.005). The majority of the sample were: female (63.4%), and the prevalent age range it was between 60 and 69 years old people, with the mean age being 70.73 (SD = 7.64). However, the three different results of this research may be the basis for thoughts and actions in the attention to the oldest population, implying a status of integrality, equity on the access for this population in focus.